OPTIMALISASI PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA DENGAN SAYUR PAKIS (Stenochlaena palustris) - Fajrin, Dessy Hidayati (STIKES NGUDIA HUSADA MADURA, 2024)
Teenage who enter puberty experience very rapid growth so that the need for iron also increases to increase their growth. Teenage girls who menstruate will lose blood every month so they need twice as much iron as during menstruation. The incidence of anemia in adolescent girls in Sambas Regency is quite high. The total number of adolescents in Tekarang Village in 2023 was 1,657 people with 928 of them being adolescent girls. The number of adolescent girls who experienced anemia in the Tekarang Health Center Work Area of ​​Sambas Regency was 473 adolescent girls (51%) out of 928 adolescent girls, so additional food is needed that can increase hemoglobin. The iron in ferns can increase hemoglobin levels in the body and help reduce symptoms of anemia. The shoots or young leaves of this fern are often used as vegetables. Kalimantan people usually boil or saute ferns to be processed. The increase in Hb levels is caused by ferns containing 291.32 mg of iron per 100 mg of ingredients that can prevent anemia.